Natural history and prognostic factors for chronic hepatitis type B. Issue 3 (March 1991) - Fattovich, G; Brollo, L; Giustina, G; Noventa, F; Pontisso, P; Alberti, A; Realdi, G; Ruol, A
Abstract : One hundred and five hepatitis B surface antigen (HBsAg) positive patients presenting with chronic persistent hepatitis (n = 46) or chronic active hepatitis without cirrhosis (n = 59) were followed longitudinally for one to 16 years (mean 5.5 years) and underwent follow up biopsy. During a mean histological follow up of 3.7 years, active cirrhosis developed in 21 (20%) patients one to 13 years after entry to the study with a calculated annual incidence of 5.9%. The probability of evolution to cirrhosis was significantly higher in patients with chronic active hepatitis and bridging hepatic necrosis than in those with moderate chronic active hepatitis or chronic persistent hepatitis (p less than 0.0001). Cox multiple regression analysis showed that the following three variables independently implied poor prognosis: older age, presence of bridging hepatic necrosis, and persistence of hepatitis B virus DNA in serum (p less than 0.0001). These findings indicate that patients with severe chronic active hepatitis and persistent hepatitis B virus replication are at very high risk of rapid progression to cirrhosis.